Breath holding duration as a measure of distress tolerance: examining its relation to measures of executive control - Sütterlin, Stefan; Schroijen, Mathias; Constantinou, Elena; Smets, Elyn; Van den Bergh, Omer; Van Diest, Ilse (Frontiers in Psychology, 2013)
Recent research considers distress (in)tolerance as an essential component in the development of various forms of psychopathology. A behavioral task frequently used to assess distress tolerance is the breath holding task. Although breath holding time (BHT) has been associated with behavioral outcomes related to inhibitory control (e.g., smoking cessation), the relationship among breath holding and direct measures of executive control has not yet been thoroughly examined. The present study aims to investigate the relationship between a series of executive function tasks and breath holding duration. Furthermore, we assessed the BHT-task’s test-retest reliability in a one-year follow-up. 113 students completed an initial BHT assessment, 58 of which also completed a series of executive function tasks (the Wisconsin Card Sorting Test, the Parametric Go/No-Go task and the N-back memory updating task). A subsample of these students (N = 34) repeated the breath holding task in a second session one year later. Test-retest reliability of the BHT-task over a one year period was high (r = .67, p